Towards an Alternative Concept of Privacy - Fuchs, Christian (Journal of Information, Communication and Ethics in Society)

A Contribution to the Critique of the Political Economy of Google - Fuchs, Christian (Fast Capitalism)

The Contemporary World Wide Web: Social Medium or New Space of Accumulation? - Fuchs, Christian (The Political Economies of Media. The Transformation of the Global Media Industries)

Cognitive Capitalism or Informational Capitalism? The Role of Class in the Information Economy - Fuchs, Christian (Cognitive Capitalism, Education and Digital Labor)

Two New Critical Internet Studies-Books: Marcus Breen’s “Uprising” and Eran Fisher’s “Media and New Capitalism in the Digital Age” - Fuchs, Christian (tripleC – Journal for a Global Sustainable Information Society)

Critical Media and Communication Studies Today. A Conversation - Fuchs, Christian; Winseck, Dwayne (tripleC)

"BlackBerry-Riots": Gewalt hat andere Gründe [“BlackBerry-Tiots“: Violence has Other Causes“] - Fuchs, Christian (Futurezone)

“Twitter Mobs“ and the Structural Violence of Neoliberalism - Fuchs, Christian (Counterfire)

Review of “The problem of order in the global age. Systems and mechanisms“ (Andreas Pickel) - Fuchs, Christian (Philosophy of the Social Sciences)

‚Grundlegende Betrachtungen zur Technik – Technomorphologische Analysen des Textilen’ - Kraft, Kerstin

‚Glamour und Grauen. Das Erforschen und Ausstellen von Bekleidung aus den 1930er und 1940er Jahren’ - Kraft, Kerstin

Cutting Patterns - Kraft, Kerstin

Photoluminescence Properties of Ordered Mesoporous ZnO - Chernikov, Alexej; Horst, Swantje; Waitz, Thomas; Tiemann, Michael; Chatterjee, Sangam (The Journal of Physical Chemistry C)
Nanoporous ZnO powders with high surface-to-mass ratios (SMR) between 15 and 70 m2 g−1 are synthesized, structurally characterized, and studied by time-resolved photoluminescence (PL). A strong dependence of the recombination dynamics and spectral width on SMR is observed at T = 10 K, and pronounced disorder-induced effects are found in the temperature dependence. Both the thermally induced shift of the PL maximum and the spectrally integrated PL intensity are interpreted by appropriate theoretical models. This consistent quantitative analysis of the experimental data yields a characteristic energy of 15 meV for the disorder scale in the nanoporous ZnO sample with an intermediate SMR.

Analysis of Existing Empirical Research Methods for Studying (Online) Privacy and Surveillance - Sevignani, Sebastian; Kreilinger, Verena; Allmer, Thomas; Fuchs, Christian

Towards a Critical Theory of Surveillance Studies - Allmer, Thomas

Critical Surveillance Studies in the Information Society - Allmer, Thomas (tripleC)

Bildung MACHT Gesellschaft

Study on the Performance Enhancement of ZnO Nanoparticles Thin-Film Transistors - Vidor, Fábio Fedrizzi; Wirth, Gilson Inácio; Wolff, Karsten; Hilleringmann, Ulrich (ECS Transactions)
Due to the electrical, sensory and optical properties the interest on ZnO-based devices including thin-film transistors (TFT) aroused. The main concerns, when using ZnO nanoparticles (NP-ZnO) in TFT, are the low charge carrier mobility and the hysteresis when poly(4-vinylphenol) (PVP) is used as gate dielectric. It is well-known that the mobility in NP-ZnO films can be enhanced by the subsequent hydrothermal decomposition of zinc salts. The electrical behavior as a function of time and temperature is investigated, taking the NP-ZnO without addition of zinc acetate as reference. The addition of zinc acetate leads to a device with better performance, with increased drain current level and without the presence of the hysteresis in the transfer characteristic. The formation reaction was performed at a temperature of 200°C, which enables process compatibility to some plastic substrates.
Keywords: General Medicine

Solution processed inverter based on zinc oxide nanoparticle thin-film transistors with poly(4-vinylphenol) gate dielectric - Wolff, K.; Hilleringmann, Ulrich (Solid-State Electronics)
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Characterization of SiON integrated waveguides via FTIR and AFM measurements - Frers, Torsten; Hett, Thomas; Hilleringmann, Ulrich; Berth, Gerhard; Widhalm, Alex; Zrenner, Artur (2011 Semiconductor Conference Dresden)

Modeling and simulation of arbitrary ordered nonlinear charge-pump phase-locked loops - Wiegand, C.; Hangmann, C.; Hedayat, C.; Hilleringmann, Ulrich (2011 Semiconductor Conference Dresden)

Semiconductor nanoparticles for electronic device integration on foils - Hilleringmann, Ulrich; Wolff, K.; Assion, F.; Vidor, F. F.; Wirth, G. I. (IEEE Africon '11)

Plane wave spectrum expansion from near-field measurements on no-planar lattices - Reinhold, C; Hangmann, C; Mager, T; Hedayat, C; Hilleringmann, Ulrich (Proc. 5th Int. Conf. on electromagnetic Near-field Characterization and Imaging (ICONIC) 2011)

Krisen der Autorschaft bei Bruckner und Reger als Insignien der beginnenden musikalischen Moderne - Höink, Dominik; Jacob, Andreas (Autorschaft. Ikonen – Stile – Institutionen)

Anton Bruckner und Franz Liszt. Zur Konstruktion kirchenmusikalischer Idealbilder - Höink, Dominik (Kirchenmusikalisches Jahrbuch)

Calculus-based optimization of the electron dynamics in nanostructures - Meier, Torsten; Reichelt, Matthias; Walther, A. (Photonics and Nanostructures - Fundamentals and Applications)
For numerous applications, the computation and provision of exact derivative information plays an important role for optimizing the considered system. This paper introduces the technique of algorithmic differentiation, a method to compute derivatives of arbitrary order within working precision. This derivative information will be combined with a calculus-based optimization algorithm to optimize a non-trivially shaped laser pulse which coherently steers the electron dynamics in a semiconductor quantum wire. Numerical results illustrating the cost for the derivative computation and the optimization process are presented and discussed.

Nachhaltiger Konsum. Neoliberale Subjekte zwischen grünem Lifestyle und gesellschaftlicher Verantwortung - Hälterlein, Jens (Gesellschaftliche Ökologie. Beiträge zur Konstruktion geographischer Wirklichkeiten. Sozialgeographische Manuskripte)

Weder Konsumismus noch Askese – Interpassivität! Über das kritische Potential des SUV-Fahrens - Hälterlein, Jens (Wir sind nie aktiv gewesen. Interpassivität zwischen Kunst- und Gesellschaftskritik)

Zwischen Sprachspiel und Methode. Perspektiven der Diskursanalyse - Feustel, Robert; Schochow , Maximilian (BEHEMOTH A Journal on Civilisation)

Finite Symplectic Matrix Groups - Kirschmer, Markus (Experimental Mathematics)
This paper classifies the maximal finite subgroups of SP₂ₙ(Q) for 1⩽n⩽11 up to GL₂ₙ(Q) conjugacy in .
Keywords: General Mathematics

Kommentar aus religionspädagogischer Sicht - Hymnologiedidaktische Überlegungen - Schroeter-Wittke, Harald (Singen im Gottesdienst. Ergebnisse und Deutungen einer empirischen Untersuchung in evangelischen Gemeinden)

Auf der Suche nach der Identität Europas - Kultur als transformatorische Kraft - Schroeter-Wittke, Harald (Perspektiven für ein Europa im Zeitalter der Globalisierung. 60 Jahre Evangelische Akademie Villigst / Iserlohn)

Den Schein wahren. Neun Responsorien auf das praktisch-theologische Interesse an den Oberflächen - Schroeter-Wittke, Harald (Lebenswissenschaft Praktische Theologie?)

Schaut hin! Rede für die Gedenkfeier am 2. April 2008 - Schroeter-Wittke, Harald (So fern und doch so nah... Wider das Vergessen)

Wewelsburg - Religionssensibilität an einem Ort des Schreckens - Schroeter-Wittke, Harald; Arnhold, Oliver (Religionssensible Schulkultur)

Hochkultur oder Popkultur? - Schroeter-Wittke, Harald; Marti, Andreas (Reformierte Liturgik - kontrovers)

Religionssensible Musik - Eine Klangreise - Schroeter-Wittke, Harald (Religionssensible Schulkultur)

Was ist Religionssensibilität? - Schroeter-Wittke, Harald (Religionssensible Schulkultur)

Intensity dependence of optically-induced injection currents in semiconductor quantum wells - Pochwala, Michal; Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (CLEO:2011 - Laser Applications to Photonic Applications)
The intensity dependence of optically-induced injection currents in semiconductor quantum wells is investigated numerically. Oscillatory behavior of the electron charge current transients as function of intensity and time is predicted and explained.
Keywords: tet_topic_qw

Simulation of Mutual Coupling of Photonic Crystal Cavity Modes and Semiconductor Quantum Dots - Declair, S.; Song, X.; Meier, Torsten; Förstner, Jens (THE FOURTH INTERNATIONAL WORKSHOP 2011)
We present numerical results of the mutual coupling between photonic crystal cavities and semiconductor quantum dots. Normal mode splitting between a single cavity mode and a single quantum dot is shown under weak excitation, while under strong excitation Q‐factor dependent side bands appear, according to the AC‐Stark effect. Coupled photonic crystals, aligned parallel but displaced under a 30°‐angle for efficient coupling, show line splittings of all eigenmodes, if a single eigenmode is resonantly coupled to a single quantum dot. The mutual coupling of N resonant quantum dots to a single cavity mode results in a N−−√ scaling of the splitting, known from quantum optics, but corrected by the field amplitude fraction for not collocated quantum dots.
Keywords: tet_topic_phc; tet_topic_qd

Wavelet‐Based Adaptive Computations of the Excitonic Eigenstates of Disordered Semiconductor Quantum Wires - Meier, Torsten; Mollet, Christian; Kunoth, Angela (AIP Conference Proceedings)
A novel adaptive wavelet based method is presented that allows us to compute eigenvalues and eigenvectors of the electronic Schrödinger equation. Our method outperforms direct discretization methods with equidistant grid spacings, in particular, for problems that involve several length scales. As an application we present numerical evaluations of the energetically lowest exciton states for ordered and disordered semiconductor quantum wires.

Theoretical approach to the ultrafast nonlinear optical response of metal slabs - Wand, Mathias; Schindlmayr, Arno; Meier, Torsten; Förstner, Jens (CLEO:2011 - Laser Applications to Photonic Applications)
We present an ab-initio method for calculating nonlinear and nonlocal optical effects in metallic slabs with sub-wavelength thickness. We find a strong localization of the second-harmonic current at the metal-vacuum interface.
Keywords: tet_topic_shg

High Performance Active Elements for Agricultural Machines Made of Ultra High-Strength Steels - Homberg, Werner; Rostek, Tim (Key Engineering Materials)
This article will highlight various aspects of the production process of high performance active elements made of ultra high-strength steels. Focus is put on the processing of thick sheet metal regarding hot forming by means of punching, embossing, and forging processes as well as on thermo-mechanical treatment. Due to the material thickness of the semi-finished parts/blanks used and owing to the high strength of the materials (Rm > 2600 MPa) current production techniques and parameters from the field of thin sheet metal can only be limitedly be transferred and have therefore been specially investigated for this application.

Presshärten von Rohren und Profilen mittels formlos fester Stoffe - Mennecart, Thomas; Rostek, Tim; Witulski, Jörg; Brosius, Alexander; Takkaya, A. Erman; Homberg, Werner

High Performance Active Elements for Agricultural Machines Made of Ultra High-Strength Steels - Homberg, Werner; Rostek, Tim (Proceedings. of the 10th International Conference on Technology of Plasticity (ICTP))

Teaching & Learning Guide for: New Media, Web 2.0 and Surveillance - Fuchs, Christian (Sociology Compass)

New Media, Web 2.0 and Surveillance - Fuchs, Christian (Sociology Compass)

Preface - Fuchs, Christian (İletişimi anlamak (Understanding communication), 4th revised)

The Political Economy of Privacy on Facebook - Fuchs, Christian

The Political Economy of Privacy - Fuchs, Christian

Analysis of Existing Empirical Research Methods for Studying (Online) Privacy and Surveillance - Sevignani, Sebastian; Kreilinger, Verena; Allmer, Thomas; Fuchs, Christian

X-ray absorption near-edge spectroscopy investigation of the oxidation state of Pd species in nanoporous SnO2 gas sensors for methane detection - Wagner, T.; Bauer, M.; Sauerwald, T.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
We report the correlation of the aging of Pd-doped SnO2 methane sensors with the change of the oxidation state of Pd. Mesoporous SnO2 doped with palladium species was prepared and exposed to different gas mixtures at high temperature (600 °C) to simulate long term usage. After each exposure step a fraction of the sample was cooled down to “freeze” the current oxidation state of Pd which was then analyzed by X-ray Absorption Near-Edge Spectroscopy (XANES) using the 'white line' (i.e. the absorption peak corresponding to the transition from the 2p3/2 core level to unoccupied 4 d states) intensity of the L(III) edge as a probe for the oxidation state. The Pd oxidation state correlates with the response of the resistive SnO2 sensor to methane gas, as determined by measuring the gas response to different concentrations of methane. Samples treated with 5000 ppm methane in air show a significant reduction of Pd(II) to Pd(0), depending clearly on the carrier gas (synthetic air, pure nitrogen) and on the temperature (600 °C vs. 300 °C).

A High Temperature Capacitive Humidity Sensor Based on Mesoporous Silica - Wagner, Thorsten; Krotzky, Sören; Weiß, Alexander; Sauerwald, Tilman; Kohl, Claus-Dieter; Roggenbuck, Jan; Tiemann, Michael (Sensors)
Capacitive sensors are the most commonly used devices for the detection of humidity because they are inexpensive and the detection mechanism is very specific for humidity. However, especially for industrial processes, there is a lack of dielectrics that are stable at high temperature (>200 °C) and under harsh conditions. We present a capacitive sensor based on mesoporous silica as the dielectric in a simple sensor design based on pressed silica pellets. Investigation of the structural stability of the porous silica under simulated operating conditions as well as the influence of the pellet production will be shown. Impedance measurements demonstrate the utility of the sensor at both low (90 °C) and high (up to 210 °C) operating temperatures.

Micrometer-sized nanoporous tin dioxide spheres for gas sensing - Smått, J.-H.; Lindén, M.; Wagner, T.; Kohl, C.-D.; Tiemann, Michael (Sensors and Actuators B: Chemical)
We report the synthesis of mesoporous tin dioxide (SnO2) materials with well-defined particle morphology. The products consist of uniform spheres with a diameter of 5 μm. The spheres are hierarchically porous with two distinct pore modes of 5.0 nm and 52 nm, respectively. This special porosity is the result of a synthesis procedure which involves a ‘hard templating’ (nanocasting) process. The product forms an approximately homogeneous monolayer of spheres on a sensor substrate and shows promising response to methane gas with low cross-sensitivity to water. The structural properties and gas-sensing performance are compared with a mesoporous SnO2 material without defined morphology, prepared by a ‘soft templating’ procedure.

Photocatalytic ozone sensor based on mesoporous indium oxide: Influence of the relative humidity on the sensing performance - Wagner, T.; Hennemann, J.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
Mesoporous In2O3, synthesized by a nanocasting procedure, is used as a resistive gas sensor for ozone in very low concentrations (from 20 ppb to 2.4 ppm) at room temperature. Its sensing performance is substantially increased by illumination with blue light (460 nm, 2.7 eV). For low ozone concentrations the sensor response increases with increasing humidity. However, higher humidity also results in the occurrence of a saturation of the response at lower ozone concentrations; this is rationalized by assuming a poisoning of surface active sites by hydroxyl groups.

A Critical Contribution to Theoretical Foundations of Privacy Studies - Allmer, Thomas (Journal of Information, Communication & Ethics in Society)

Piezoelectric sensor array with evaluation electronic for counting grains in seed drills - Meyer zu Hoberge, S.; Hilleringmann, Ulrich; Jochheim, C.; Liebich, M. (IEEE Africon '11)

Die Rezeption der Kirchenmusik Anton Bruckners. Genese, Tradition und Instrumentalisierung des Vergleichs mit Giovanni Pierluigi da Palestrina - Höink, Dominik
Einen 'modernen Palestrina' nennt Max Auer den Komponisten Anton Bruckner und pointiert damit eine noch heute virulente Vorstellung, die den katholisch-frommen Bruckner auf einer Linie mit dem durch die Retterlegende glorifizierten und päpstlicherseits kanonisierten Ideal Giovanni Pierluigi da Palestrina sieht. Diese stil- und rezeptionsgeschichtliche Untersuchung richtet aus diachroner Perspektive den Blick auf Genese und Tradierung dieses Komponistenvergleichs vom 19. Jahrhundert bis in die Gegenwart. Im Zentrum steht dabei die Analyse des maßgeblichen wissenschaftlichen Bruckner-Schrifttums und seiner kontextuellen Verortung innerhalb der bisweilen höchst ideologisch aufgeladenen musikgeschichtlichen Diskurse. Ferner werden auf der Basis neuer Quellen die Kanonisierungsbestrebungen hochrangiger Vertreter der Bruckner-Gesellschaft im Rahmen der sogenannten 'Aktion Rom' ausgewertet, die für die Instrumentalisierung des Vergleichs von zentraler Bedeutung sind. Es folgt eine Analyse derjenigen Kompositionen, die in die Nähe des Palestrina-Stils gerückt wurden. Am Ende der Arbeit steht eine Neubewertung des Vergleichs auf der Grundlage der aus Rezeptionsgeschichte und Analyse gewonnenen Ergebnisse.

Injection currents in (110)-oriented GaAs/AlGaAs quantum wells: recent progress in theory and experiment - Duc, H. T.; Pochwala, M.; Förstner, Jens; Meier, Torsten; Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M. (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XV)
We experimentally and theoretically investigate injection currents generated by femtosecond single-color circularly-polarized laser pulses in (110)-oriented GaAs quantum wells. The current measurements are performed by detecting the emitted Terahertz radiation at room temperature. The microscopic theory is based on a 14 x 14 k • p band-structure calculation in combination with the multi-subband semiconductor Bloch equations. For symmetric GaAs quantum wells grown in (110) direction, an oscillatory dependence of the injection currents on the exciting photon energy is obtained. The results of the microscopic theory are in good agreement with the measurements.
Keywords: tet_topic_qw

Electron g-factor anisotropy in symmetric (110)-oriented GaAs quantum wells - Hübner, J.; Kunz, S.; Oertel, S.; Schuh, D.; Pochwała, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten; Oestreich, M. (Physical Review B)
We demonstrate by spin quantum beat spectroscopy that in undoped symmetric (110)-oriented GaAs/AlGaAs single quantum wells, even a symmetric spatial envelope wave function gives rise to an asymmetric in-plane electron Land´e g-factor. The anisotropy is neither a direct consequence of the asymmetric in-plane Dresselhaus splitting nor a direct consequence of the asymmetric Zeeman splitting of the hole bands, but rather it is a pure higher-order effect that exists as well for diamond-type lattices. The measurements for various well widths are very well described within 14 × 14 band k·p theory and illustrate that the electron spin is an excellent meter variable for mapping out the internal—otherwise hidden—symmetries in two-dimensional systems. Fourth-order perturbation theory yields an analytical expression for the strength of the g-factor anisotropy, providing a qualitative understanding of the observed effects.
Keywords: tet_topic_qw

Microscopic theory of the extremely nonlinear terahertz response of semiconductors - Golde, D.; Kira, M.; Meier, Torsten; Koch, S.W. (physica status solidi (b))
The extreme nonlinear terahertz response of initially unexcited intrinsic semiconductor nanostructures is studied theoretically by solving extended semiconductor Bloch equations numerically. The coupled dynamics of intraband acceleration and multiphoton interband transitions leads to high-harmonic generation up to several tens of the exciting terahertz frequency. It is shown that the actual cut-off frequency is determined by the band structure and not by the excitation strength.

Singen im Gottesdienst - Eine empirische Untersuchung - Schroeter-Wittke, Harald; Heye, Andreas; Gembris, Heiner (Singen im Gottesdienst. Ergebnisse und Deutungen einer empirischen Untersuchung in evangelischen Gemeinden)

Religionssensible Schulkultur

Die Zukunft der Orgel angesichts der Vielfalt christlicher Gottesdienste - Gemeindekulturpädagogische Beobachtungen - Schroeter-Wittke, Harald (Die Orgel zwischen gestern und morgen)

Singen im Gottesdienst. Ergebnisse und Deutungen einer empirischen Untersuchung in evangelischen Gemeinden

Überzeichnet - Religion in Comics

Simsalabimbambasaladusalasim. Zwischenbilanz einer Performativen Religionspädagogik - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Motion and Emotion. Theologische Overtüre zum Thema Tanz und Religion - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/70/hsw13.htm)

Sexagesimae. 2Kor (11,18.23b-30) 12,1-10: Karneval mit Paulus - Eine Zuspitzung - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

6. Sonntag nach Trinitatis. 5. Mose 7,6-12: Keine Kleinigkeit, oder: Wem die Phantasie durchgeht - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien III/2)

Popkultur als Herausforderung für die Kirchenmusik - Schroeter-Wittke, Harald (Liturgie und Kultur)

Gleichnis der Welt in Tönen. Zum 100. Todestag von Gustav Mahler - Schroeter-Wittke, Harald (Praktische Theologie)

Carla's Christmas Carols. Carla Bleys unorthodoxe Weihnacht - Schroeter-Wittke, Harald (Praktische Theologie)

Protestsongs.de - Schroeter-Wittke, Harald (Praktische Theologie)

"So reden wir immer!". Der Einfluss der Medien auf das Sprachverhalten junger Migranten in Deutschland - Günesli, Habib (tv diskurs)
Neue Medien eröffnen neue Möglichkeiten der Kommunikation und bringen neue sprachliche Erscheinungsformen zutage. Im Rahmen seiner Wissenschaftlichen Hausarbeit für die Erste Staatsprüfung für das Lehramt an Grund- und Hauptschulen hat sich der Autor mit dem Mediennutzungsverhalten und dessen Auswirkung auf die Sprachkompetenz junger türkischer Migranten beschäftigt.

Photocurrents in semiconductor carbon nanotubes with spin-orbit interaction - Meier, Torsten; Liu, Hong; Duc, Huynh Thanh; Schumache, Stefan (75. Annual meeting of the DPG and combined DPG Spring meeting)
In recent years, single-walled carbon nanotubes (SWCNTs) have received widespread attention due to their perfect quasi-one-dimensional structure and unique physical properties, as well as their potential for applications. In the present work, we calculate the band structure of SWCNTs using an atomistic tight-binding model including spin-orbit interaction. We combine this approach with a many-particle calculation of the nonlinear optical response using multi-band semiconductor Bloch equations. We show that, for SWCNTs lacking inversion symmetry, the intrinsic spin-orbit interaction can give rise to single-color photoinduced charge and spin currents. In particular, we study the influence of excitonic effects on these photoinduced currents and draw the analogy to recent investigations on single-color injection of photocurrents in semiconductor quantum wells.

Analysis of multidimensional Fourier transform spectroscopy for semiconductors with a phenomenological level model - Meier, Torsten; Wiebeler, Christian; Reichelt, Matthias (75. Annual meeting of the DPG and combined DPG Spring meeting)
Optical two-dimensional Fourier transform spectroscopy has been used to study the properties of semiconductor nanostructures in four-wave-mixing like experiments. Applying a phenomenological level model, we numerically and analytically analyze the main features of excitonic and biexcitonic contributions in a semiconductor quantum well by solving the optical Bloch equations. The method is extended to three-dimensional Fourier transform spectroscopy to investigate a recent experiment.

Extreme nonlinear optics in semiconductors with shaped laser pulses - Meier, Torsten; Reichelt, Matthias; Walther, Andrea (75. Annual meeting of the DPG and combined DPG Spring meeting)
If a two-level system is excited with an intense light field of several times the Rabi frequency, the well-known Mollow triplets appear in the emitted radiation spectrum. We show that the pattern of the emission spectrum can be changed by using appropriately shaped laser pulses. The effect is also observable for a more realistic description of a semiconductor system.

„Kutte & Co.“ – Zur textilen SchriftBildlichkeit des Heavy Metals - Eckel, Julia (Metal Matters – Heavy Metal als Kultur und Welt)

Tilting on non–commutative rational projective curves - Burban, Igor; Drozd, Yu. (Mathematische Annalen)

Mars-Viskurse. De- und Re-Kontextualisierungen von wissenschaftlichen Bildern - Adelmann, Ralf (Blickregime und Dispositive audiovisueller Medien)

Von der Freundschaft in Facebook - Adelmann, Ralf (Generation Facebook. Über das Leben im Social Net)

"Oh, Oh, Oh, let's count some more." Hochschulrankings als mediale Form - Adelmann, Ralf (Zeitschrift für Medienwissenschaft 1/2011)

Supportive and hindering factors to a sustainable implementation of ICT in schools - Eickelmann, Birgit (Journal for Educational Research Online/Journal für Bildungsforschung Online)

Restructuring educational systems to move into the digital age. Report of EduSummIT 2011 - Davis, Niki; Eickelmann, Birgit; Schulz-Zander, Renate (International Summit of ICT in Education: Building a Global Community of Policy-Makers, Educators, and Researchers to Move Education into the Digital Age)

Wirkungen digitaler Medien - Herzig, Bardo; Grafe, S. (Schule in der digitalen Welt. Medienpädagogische Ansätze und Schulforschungsperspektiven)

Medienkompetenz – Grundbegriffe, Kompetenzmodelle, Standards. - Herzig, Bardo; Grafe, S. (Kompetenzorientierung in Schule und Lehrerbildung. Perspektiven der bildungspolitischen Diskussion, der Bildungsforschung und der Mathematik-Didaktik)

Zukunftsfähige Lernkultur - Herzig, Bardo; Grafe, S. (Bildung Spezial. Friedrich Jahresheft 3/2011)

Religionssensible Schulkultur aus erziehungswissenschaftlicher Sicht - Freitag, Christine (Religionssensible Schulkultur)

Anpassen, verändern, abschaffen? Schulische Leistungsbewertung in der Diskussion

Wie muss die schulpraktisch orientierte Lehrerbildung die schulischen Veränderungen aufnehmen? - Freitag, Christine (Schulpraxisstudien in Europa)

How Hydrogen Bonds Influence the Mobility of Imidazolium-Based Ionic Liquids. A Combined Theoretical and Experimental Study of 1-n-Butyl-3-Methylimidazolium Bromide - Kohagen, M.; Brehm, Martin; Lingscheid, Y.; Giernoth, R.; Sangoro, J.; Kremer, F.; Naumov, S.; Iacob, C.; Kärger, J.; Valiullin, R.; Kirchner, B. (J. Phys. Chem. B)

Performance of Quantum Chemically Derived Charges and Persistence of Ion Cages in Ionic Liquids. A Molecular Dynamics Simulations Study of 1-n-Butyl-3-Methylimidazolium Bromide - Kohagen, M.; Brehm, Martin; Thar, J.; Zhao, W.; Müller-Plathe, F.; Kirchner, B. (J. Phys. Chem. B)

Singular Value Decomposition for Analyzing Temperature- and Pressure-Dependent Radial Distribution Functions: Decomposition into Grund RDFs (GRDFs) - di Dio, P. J.; Brehm, Martin; Kirchner, B. (J. Chem. Theory Comput.)

Ab initio Molecular Dynamics Simulations of a Binary System of Ionic Liquids - Brüssel, M.; Brehm, Martin; Voigt, T.; Kirchner, B. (Phys. Chem. Chem. Phys.)

TRAVIS – A Free Analyzer and Visualizer for Monte Carlo and Molecular Dynamics Trajectories - Brehm, Martin; Kirchner, B. (J. Chem. Inf. Model.)

Produktionsverfahren zur Herstellung höchstfester hybrider Leichtbaustrukturen für den Einsatz im Automobil - Lauter, Christian; Damerow, Ulf; Frantz, Meike; Tröster, Thomas; Homberg, Werner

Manufacturing processes for automotive structures in multi-material design consisting of sheet metal and CFRP prepregs - Lauter, Christian; Dau, J.; Tröster, Thomas; Homberg, Werner

Multi-material systems. High strength steels and fiber-reinforced plastics - Lauter, Christian; Sköck-Hartmann, Britta; Gries, Thomas; Tröster, Thomas; Linke, Markus

Hybrid FRP-Steel components for automotive applications - Kochanek, C.; Siewers, Bernd; Frantz, Meike; Glowania, M.; Linke, M.; Lauter, Christian; Gries, Thomas; Tröster, Thomas